Intelectuais e "folclore" em Sergipe : um estudo sobre a Comissão Sergipana de Folclore (1948-1976) - Sales, Tatiana Silva (2018)
The Folkloric Commission of Sergipe – FCS, which is the aim of this study, was originated in 1948 as an initiative of the Brazilian "folkloric movement" institutionalized through the National Folklore Commission, created in 1947 to promote peace and diversity undertaken by UNESCO during postwar. FCS has gathered intellectuals throughout its seventy years of existence. Many of them have been linked to other cultural institutions of Sergipe, such as Academy of Letters, Historical and Geographical Institute of Sergipe, Federal University of Sergipe, State Secretary of Culture, Music Institute, Catholic Philosophy School of Sergipe and Society of Artistic Culture of Sergipe. Thus, some questions are relevant to this study in order to identify those professionals who worked with FCS and were extremely important to the institution throughout its existence and actions that they undertook; what role they owned; the reason why folklore is chosen as a "cause" by this social group and how its articulation with the orientation of defense policies of the Brazilian folklore in association with federal entity and locals. In addition, what conceptions of folklore were developed and diffused from them in their "places of speech". In agreement to it, the objective is to draw up an approach that helps to expand the understanding of what is conceived as folklore in Sergipe - since it is known as a consistent social and historical category - through the contribution of intellectuals who were part of the FCS. As such, this work has been structured in three chapters, in order to provide a contribution to the trajectory of folklore studies in Sergipe. This perspective aims at achieving a socio-historical insertion in groups that have thought and used categories of "folklore", "popular culture", "people" and "politics". Finally, this study shows the relevance of understanding how individuals that belong to Folkloric Commission of Sergipe contributed, by these conceptions, to the institutionalization titled as "folklore studies" in Sergipe. That contribution can be seen as a translation of different levels of articulations among Civil Society institutions, public law and university for bestowing to status folklore under different approaches inside FCS itself: “people's knowledge”, “tradition”, “essence” that should be studied, comprehended, propagated, preserved and kept as a living expression of “culture” and “identity” of Sergipe.